Attitude, subjective norms, and environment friendly as antecedents of customer purchase behavior - Hafidzah, Fitri Nur (Universitas Ahmad Dahlan, 2024)
Purpose-Consumer purchasing behavior towards a product is certainly influenced by various factors, both internal and external. This study aims to determine the effect of attitudes, subjective norms, and environment friendly on consumer purchasing behavior. These factors have a positive impact on consumer purchasing behavior. Design/Methodology/Approach-This research focuses on Tokopedia e-commerce users in Yogyakarta, Indonesia. The total research sample consists of 96 respondents, who were surveyed using a purposive sampling technique. The research data is primary data obtained through questionnaire distribution. Data analysis was carried out using SPSS version 25. Findings-The results of this study prove that attitude has a positive but insignificant effect on consumer purchasing behavior. Subjective norms and a friendly environment have a partial positive impact on consumer purchasing behavior. The subjective norms adopted by consumers and their concern for the environment influence consumers when purchasing a product. However, this attitude has proven insignificant in influencing consumer purchasing behavior because other factors, such as the other two variables, are more significant in influencing consumer purchasing behavior. Research limitations/implications-The research is limited to a small number of respondents and only examines users of the Tokopedia e-commerce application in Yogyakarta, Indonesia. Therefore, the results of this study cannot be used as a reference to describe consumer purchasing behavior among e-commerce users in general and in various regions of Indonesia. Originality/value-Previous research has not analyzed the factors that influence consumer purchasing behavior as in this study, especially for Tokopedia e-commerce users in Yogyakarta. Previous research analyzes different aspects and uses different research objects as well.